LINEAR SIMPLE SYMMETRICAL PROCRUSTES TRANSFORMATION - V. S. Mukha; A. N. Kuzkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It is designed the Linear transformation of usual (two-dimensional) matrixes, which is named as simple symmetrical Procrustes transformation. The offered transformation can be used in recognition of the graphic presentations of physical objects and in decision of other problems.